Regional Variations in rpoB Gene Mutations and Their Association with Rifampicin Resistance in Mycobacterium tuberculosis - Widodo, Widodo; Wahyono, Daniel Joko; Oedjijono, Oedjijono; Pramono, Hendro (Molekul, 2025)
ABSTRACT. The increasing incidence of tuberculosis (TB) remains a global challenge, driven by the emergence of Mycobacterium tuberculosis resistance to antituberculosis drugs. This study investigated the relationship between rpoB gene mutations, rifampicin resistance levels, and the geographic origin of multidrug-resistant M. tuberculosis (MDR-TB) isolates. A total of 30 MDR-TB isolates were collected from the Central Java Provincial Health and Calibration Testing Laboratory between January and December 2023. Rifampicin resistance levels ranged from 5 to 80 µg/mL and were assessed using the microculture method, while DNA sequencing identified rpoB mutations. The results showed that rifampicin exposure significantly influenced rpoB mutation frequencies, with Ser531Leu (50%), His526 (16.7%), Leu511 (6%), Leu533 (6%), and Gln513 (6%) being the most common. Geographic variations were observed, with isolates from the ex-residencies Pekalongan, Pati, and Banyumas Residencies harboring seven, six, and four distinct mutations, respectively. Mutations such as Leu511Arg+His526Ser and Asp516Val were detected at low rifampicin concentrations (5–10 µg/mL), whereas Ser531Leu mutations dominated at moderate levels (20–80 µg/mL). These findings confirmed that rpoB mutations were influenced by both the region of origin and rifampicin resistance levels, providing critical insights for improving TB diagnosis and optimizing MDR-TB treatment strategies. Keywords: Mycobacterium tuberculosis, rifampicin resistance, rpoB gene mutation